Effects of mini-implant facilitated micro-osteoperforations in alleviating mandibular anterior crowding: A randomized controlled clinical trial - Mehak Bansal; Rekha Sharma; Davender Kumar; Ambika Gupta (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVES: To investigate the effectiveness of mini-implant (MI)-facilitated micro-osteoperforations (MOPs) in accelerating mandibular anterior teeth alignment. MATERIALS AND METHODS: Thirty teenage patients with mandibular crowding (Little's irregularity index between 4 and 6 mm) were randomly allocated to either "experimental" group (micro-osteoperforation assisted alignment) or "control" group (conventional orthodontics). Blinding was done at the data analysis stages. Six MOPs were performed using MI on the labial aspect in the mandibular anterior region. The primary outcome was the overall treatment time needed to complete alignment of mandibular anterior teeth. The secondary outcomes were to compare the marginal bone height loss and volumetric root resorption around mandibular incisors along with subject's perception of pain, comfort and satisfaction. RESULTS: There was statistically significant difference in the total treatment duration for complete alignment of mandibular incisors. The completion of cases in experimental group was 43.93% times faster than the control group. There were no statistically significant differences in volumetric root resorption and marginal alveolar bone height loss around mandibular incisors as well as pain perception between the two groups. CONCLUSIONS: MI-facilitated MOPs accelerated tooth movement significantly upto nine weeks without any significant pain and discomfort, with no increase in root resorption and marginal alveolar bone height loss.